Pengaruh Brand Image dan Kualitas Produk Terhadap Loyalitas Pelanggan Produk Facial Wash Kahf Pria di Kecamatan Ciracas Jakarta Timur - Rizky Elsaputra; Niken Herawati (WORKFORCE JOURNAL: Manajemen & Bisnis, 2026)
The growth of the men’s skincare industry in Indonesia triggers intense competition. Potentially reducing customer loyalty due to brand switching. This studi aims to determine the partial and simultaneous effects of brand image and product quality on customer loyalty for men’s Kahf facial wash products in Ciracas District, East Jakarta. Using a statistical quantitative approach, the study involves a population of 153.398 men, with a a sample of 105 respondents selected via purposive sampling. Primary data was gathered through questionnaires, while secondary techniques comprised data quality tests, classic assumption tests, multiple linear regression, and hypothesis testing (t-test and f-test) using SPSS version 25. The result indicate that brand image and product quality, both partially and simultaneously, have a positive and significant effect on customer loyalty. A coefficient of determination of 60,1% show that independent variables successfully explain customer loyalty. This study concludes that reinforcing brand image and improving product quality are crucial factors in maintaining and enhancing customer loyalty.